Effects of hydrogen enrichment on compressed natural gas engine performance and emissions - Asnawi, (2011)
A quasi-dimensional thermodynamic cycle simulation with a two-zone combustion model is developed to simulate the combustion characteristics,performance and emissions of a four-cylinder spark ignition (SI) engine fueled with CNG-hydrogen blends. This model, applying the first law of thermodynamics for a closed system, is inclusive of the flame front propagation computed through geometric modeling and turbulent entrainment modeling to predict the mass fraction burned during the combustion process which is an important performance parameter for engine cycles. The hypothesis is enrichment of H2 to CNG fuel can increase burning velocity and wide-range equivalence ratio,resulting in decreasing sparks advanced and stabilize flame propagation ring combustion process. The CNG-H2 mixtures were prepared with varied hydrogen fractions from 0-40% with the increment of 10%. The engine was operated over a wide range of equivalence ratios of 0.55 to 1.2, at a constant engine speed of 3000 rpm and the intake pressure of 86,525 kPa. In addition, the spark timing for each of the tests was adjusted to achieve maximum brake torque. Simulations with Matlab were performed under different engine operating conditions. This model was successfully developed to predict characteristic combustion, engine performance and emissions, where, a good agreement was found between the experimental data and simulation results. By the addition of H2 of up to 40%, a decrease in the fuel burning duration was observed leading to a reduction of 1.5% heat loss at stoichiometric mixture. In addition, the fuel mixtures make it possible to run the engine under lean equivalence ratios due to improve the combustion stability at extremely lean conditions, so it will be improving engine brake power by increasing the hydrogen fraction. An increase in brake power of about 2.14% at 0.55 equivalence ratio was obtained, accompanied by a reduction in fuel consumption of about 9.5% at the same equivalence ratio and decreases the brake specific fuel consumption about 8.8% and 11.4% at stoichiometric and 0.55 equivalence ratio, respectively. The increase in H2 fraction also contributes to the decreasing of CO2 and CO emissions where a decrease of 14.98-15.48% and 28.87%-7.66% of CO2 and CO emissions were observed, respectively, for lean to stoichiometric mixtures. However, an increase in NO emissions of about 3.54% was observed at 10% H2. Maximum NO emissions were obtained at 0.9 equivalence ratio for all fuel mixtures including CNG fuel while lower NO emissions were obtained at leaner mixtures under 0.7 of equivalence ratio. The hypothesis for this study is accepted.